Eurypsychrophilic acidophiles: From (meta)genomes to low-temperature biotechnologies - Dopson, Mark; González-Rosales, Carolina; Holmes, David S.; Mykytczuk, Nadia (Frontiers in Microbiology, 2023)
Low temperature and acidic environments encompass natural milieu such as acid rock drainage in Antarctica and anthropogenic sites including drained sulfidic sediments in Scandinavia. The microorganisms that inhabit these environments include polyextremophiles that are both extreme acidophiles (defined as having an optimum growth pH <3) and eurypsychrophiles that grow at low temperatures down to approximately 4 °C but have an optimum temperature for growth above 15 °C. Eurypsychrophilic acidophiles have important roles in natural biogeochemical cycling on earth and potentially on other planetary bodies and moons along with biotechnological applications in for instance, low temperature metal dissolution from metal sulfides. Five low temperature acidophiles are characterized; namely Acidithiobacillus ferriphilus, Acidithiobacillus ferrivorans, Acidithiobacillus ferrooxidans, ‘Ferrovum myxofaciens’, and Alicyclobacillus disulfidooxidans and their characteristics are reviewed. Our understanding of characterized and environmental eurypsychrophilic acidophiles has been accelerated by application of ‘omics’ techniques that have aided in revealing adaptations to low pH and temperature that can be synergistic while other adaptations are potentially antagonistic. The lack of known acidophiles that exclusively grow below 15 °C may be due to the antagonistic nature of adaptations in this polyextremophile. In conclusion, this review summarizes the knowledge of eurypsychrophilic acidophiles and places the information in evolutionary, environmental, biotechnological, and exobiology perspectives.